SAT0302 Clinical and Laboratory Features of Late-Onset Psoriatic Arthritis in Comparison with Younger-Onset Disease: Data from an Early Arthritis Cohort. (23rd January 2014) - D'Angelo, S.; Gilio, M.; Palazzi, C.; Leccese, P.; Nigro, A.; Lofrano, M.; Bello, S. D.; Padula, A.; Olivieri, I.
Abstract : Background: Psoriatic arthritis (PsA) is generally observed in middle-aged patients but can also begin in the elderly. With the increasing life expectancy, it is highly likely that the number of patients with late-onset PsA will increase. Objectives: The aim of the study was to establish in a cohort of patients with early PsA whether the age at the disease onset may influence the clinical and laboratory characteristics and the performance of CASPAR criteria. Methods: Consecutive patients with a diagnosis of early (symptom duration < 52 weeks) PsA, made by rheumatologists with long-standing expertise in PsA, were recruited in a prospective study. According to the age at the onset of musculoskeletal manifestations, patients were divided into younger-onset (YOPsA) (age < 60 years) and late-onset (LOPsA) (onset age ≥ 60 years) PsA. Clinical features and sensitivity of the CASPAR criteria were studied in accordance to this age stratification. Results: During a 3-year recruitment period, 76 PsA patients (34 M, 42 F; age 49±16, range 16-90 years) with a disease duration of 20±15 weeks (range 1-52) were enrolled. Compared to the 60 patients with YOPsA, the 16 patients with LOPsA had a significant shorter disease duration (15±17 vs. 21±15 weeks, p < 0.05) and showed more frequently increased levels of ESR (75% vs. 43%, p < 0.05) and CRP (87% vs. 52%, p < 0.01) In addition, patients with LOPsA developed more frequently inflammatory extremity swelling with pitting edema (IESPE) over the dorsum of hands and/or of the feet (56% vs. 13%, p < 0.01). There were no other significant differences between the 2 groups even though more males were observed in the LOPsA group (56% vs. 42%, p > 0.05). The sensitivity of the CASPAR criteria was similar in YOPsA (78%) and LOPsA (75%). Conclusions: Among patients with early PsA, some clinical and laboratory features may differ depending on the age at disease onset. However, in contrast with previous studies on patients with PsA of longer disease duration, early LOPsA is not more severe than early YOPsA. Finally, the CASPAR criteria seem to work similarly well in early LOPsA and YOPsA. Disclosure of Interest: None Declared